(3OjhGf GdMce heYGOf Gdcdes - (3YHO GdefYe GdLdjGfj , YHO GdefYe Hf YeQ Hf MSGf GdZSGfj GdCfOdSj, CHh GdaVd,J (B602 (3g` s
(3BNQgG (B:s
(3jfJgi HBNQ MQa GdYjf GdegedI s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B459 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B780s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(add 5760) s
Keywords: (3GdCOHs